Konsep Moderasi Islam dalam Pendidikan Global dan Multikultural di Indonesia - Fitri Meliani; Aji Muhamad Iqbal; Uus Ruswandi; Mohamad Erihadiana (Eduprof : Islamic Education Journal, 2022)
The flow of globalization has dominated Indonesia as the party who is influenced, not the one who influences. Indonesia is one of the potential markets for the development of foreign cultures. This situation threatens the local culture which has a long tradition in the socio-cultural life of the Indonesian people. Aspects of education can not be separated from the effects of globalization, the rapid progress of science and technology has brought its own impact to the world of education. In recent years, many schools in Indonesia have adopted the international education system. This can be seen in schools with a bilingual approach, namely the use of foreign languages ​​such as English and Mandarin as a second language that must be used in daily life at school. Educational levels from high school to university, both public and private, have opened international class programs. The real challenge faced by the local community is the effort to maintain the value of local norms and culture. The Indonesian people must be firm, at the same time open and tolerant, so that they can filter and adopt foreign cultures that do not conflict with local norms and culture. A firm stance is needed to avoid contamination of other cultural values ​​that are contrary to local norms and culture. ABSTRAK Arus globalisasi yang berasal dari negara-negara maju telah mendominasi Indonesia sebagai pihak yang dipengaruhi, bukan yang mempengaruhi. Indonesia merupakan salah satu pasar potensial bagi perkembangan budaya asing dari negara maju. Situasi ini mengancam budaya lokal yang memiliki tradisi panjang dalam kehidupan sosial budaya masyarakat Indonesia. Aspek pendidikan tidak terlepas dari efek globalisasi, Kemajuan ilmu pengetahuan dan teknologi yang semakin pesat telah membawa dampak tersendiri bagi dunia pendidikan. Dalam beberapa tahun terakhir, banyak sekolah di Indonesia yang mengadopsi sistem pendidikan internasional. Hal ini terlihat pada sekolah dengan pendekatan dua bahasa (bilingual), yaitu penggunaan Bahasa asing seperti bahasa Inggris dan Mandarin sebagai. Tantangan yang dihadapi oleh masyarakat sesungguhnya yaitu usaha mempertahankan nilai kearifan atau budaya lokal. Bangsa Indonesia harus tegar dan teguh pendirian, sekaligus terbuka dan toleran, agar dapat menyaring dan mengambil kebudayaan asing yang tidak bertentangan dengan norma-norma dan kebudayaan lokal. Sikap teguh pendirian diperlukan untuk menghindari kontaminasi nilai budaya lain lain yang bertentangan dengan norma-norma, etika kebudayaan lokal.